PENILAIAN PROYEK BERPENDEKATAN VISUAL, AUDITORI, DAN KINESTHETIK DENGAN PRODUK STORYBOARD DAN PENERAPANNYA PADA SISWA SMA - Pamungkas, Wilis Okti (Jurnal Pendidikan Matematika dan IPA, 2016)
Authentic assessment is assessment instrument that assess the learning process and learning outcomes of students. Authentic assessment instrument which developed in this research is project assessment instrument with storyboard product. This study aims to develop project assessment instruments which are valid, reliable and effective to be used for all of the students. The research method used is the modified 4-D model. This research implemented in grade class XI of SMA N 10 Semarang and subjects of research is students in class XI with IPA concentration. The results of research showed that project assessment instruments valid, reliable, and proper to used for assessing learning process and learning outcomes. Project assessment instrument effective used in learning, because the vmean of project assessment and learning outcomes all of students gained a value with the minimum criteria of good, also there is an ascendant of N-gain with high category for students visual, student auditory, and student kinesthetic. Thus it can be concluded that the developed assessment instruments is valid, reliable, and effective. Keywords: ProjectÂ Assessment;Â Storyboard; Visual, Auditory, and Kinesthetik Approach